The Influence of Institutional Agility, Organizational Commitment, And Digital Resource Capability on The Educational Organizational Resilience of Higher Education Institutions In Indonesia - Mohzana Mohzana; Wylda O. Kowey; Dasep Supriatna; Akhmad Ramli; Swasta Bangun; Budi Akhmad Tarigan (EDUCARE: Jurnal Pendidikan dan Kesehatan, 2026)
This research aims to examine the effect of Institutional Agility, Organizational Commitment and Digital Resource Capability on Educational Organizational Resilience of Higher Education Institutions in Indonesia. The quantitative approach was performed thru a questionnaire applied to professors and administrative staff of higher education institutions throughout the country. The sampling method was purposive sampling. The data were collected thru online survey via google forms and analyzed thru multiple linear regression. The results show that Institutional Agility, Organizational Commitment and Digital Resource Capability have a positive and significant effect on Educational Organizational Resilience. The most visible effect of the three factors is Institutional Agility. These findings mean that the ability of the higher education institution to adapt to change in a timely and flexible manner with the support of the commitment of organizational members and the required digital resource capabilities is an important aspect for strengthening institutional resilience. The study indicates that higher education institutions should improve Institutional Agility by enhancing organizational flexibility, speeding up decision-making, improving coordination across units, and enhancing the ability to identify and respond to environmental changes.